Investigating the effects of excitatory and inhibitory somatosensory rTMS on somatosensory functioning in the acute and subacute phases of stroke: a preliminary double-blind and randomized trial - Gao, Jingtian; Wang, Helin; Hu, Zhouyao; He, Jiqing; Yang, Jing; Lou, Xiaokun; You, Zhiyuan; Li, Jie; Wang, Jinghua; Gao, Zhongming (Frontiers in Human Neuroscience, 2024)
Background: Repetitive transcranial magnetic stimulation (rTMS) targeting the primary somatosensory cortex (S1) has a potential effect on somatosensory functioning following a stroke. However, S1-rTMS was combined with peripheral therapies in previous trials. Moreover, these studies have commonly targeted the ipsilesional S1 with excitatory rTMS paradigms.Method: This double-blind, randomised trial (registration number: ChiCTR2200059098) investigated two forms of paradigms, that is ipsilesional excitatory and contralesional inhibitory rTMS, as a stand-alone treatment in post-stroke somatosensation. Patients in the acute and subacute phases of stroke were randomly assigned to either contralesional 1-Hz or ipsilesional 10-Hz rTMS group and received ten daily sessions of treatment in two consecutive weeks.Results indicate that the contralesional inhibitory and ipsilesional excitatory stimulation were equally effective in improving somatosensory functioning. Moreover, this effect was most prominent in deep sensations and subjective sensations. Using single-pulse EMG recordings, our data also revealed an increased MEP amplitude in the ipsilesional motor cortex following ipsilesional excitatory treatment.This preliminary study demonstrates the primary somatosensory cortex as an effective rTMS target in somatosensory recovery following stroke.